2018
DOI: 10.3389/fpls.2018.00770
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization Changes Chemical Defense in Needles of Mature Norway Spruce (Picea abies)

Abstract: Nitrogen availability limits growth in most boreal forests. However, parts of the boreal zone receive significant levels of nitrogen deposition. At the same time, forests are fertilized to increase volume growth and carbon sequestration. No matter the source, increasing nitrogen in the boreal forest ecosystem will influence the resource situation for its primary producers, the plants, with possible implications for their defensive chemistry. In general, fertilization reduces phenolic compound concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
(81 reference statements)
4
22
0
Order By: Relevance
“…The explanation for the big differences between the cohorts may be the timepoint of sampling, just after the current-year needles were fully grown, which is probably when the use of N is at its highest and the needle N concentrations at their lowest. We earlier found corresponding results in needles from mature spruce sampled at the same time of the year (Nybakken et al, 2018).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The explanation for the big differences between the cohorts may be the timepoint of sampling, just after the current-year needles were fully grown, which is probably when the use of N is at its highest and the needle N concentrations at their lowest. We earlier found corresponding results in needles from mature spruce sampled at the same time of the year (Nybakken et al, 2018).…”
Section: Discussionsupporting
confidence: 69%
“…After fertilization, more C is used for growth, and production of phenolic compounds is usually reduced (Koricheva et al, 1998). In our previous study of chronically fertilized spruce on a low fertility site, we found large reductions in low-molecular weight phenolics in current-year needles, while there was no effect on those from the previous year (Nybakken et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Flavonoids are also considered indicators of nitrogen availability in a plant (Nybakken et al, 2018). Nitrogen, as a component of the major macromolecules, is a fundamental macronutrient in plant nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly lower nitrogen balance indexes and higher flavonol indexes were recorded for irradiated plants than for the control plants, however the influence of different LED light spectra on the nitrogen balance index (NBI) was not demonstrated. Flavonoids, as non-nitrogenous secondary metabolites, are considered indicators of nitrogen availability in a plant [ 50 , 51 ]. The flavonoid content increases under low N availability [ 36 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%